Walking on a Tight Rope: Sri Lanka's Fragile Transitional Justice Process - Medawatte, Danushka (Harvard Human Rights Journal, 2017)
The Sri Lankan Transitional Justice (“TJ”) process, which commenced primarily at the end of the war in 2009, and then gained momentum after the change of administration in early 2015, is wrought with controversies. This is mainly caused by the inability to strike balances and reach compromises when and where necessary. The laws and institutions that were recently established in Sri Lanka2 in response to rising demands for TJ appear to be mere white elephants which are struggling to address the mammoth remnants that have transcended temporal, geographical and political markers of the war. The tug of war between the ‘joint opposition’ and the ‘unity government’ has created political instabilities and slowed the current administration’s attempts to introduce TJ. This has been rather unnerving for those who have been compelled to live without remedies for past violations for a prolonged period. The general public of Sri Lanka has therefore lost confidence in the TJ process. The international pressure that has been mounting and Sri Lanka’s laboring responses to TJ have only added to existing controversies by facilitating the fears of the masses that the hard won ‘sovereignty’ is now threatened by ‘international conspiracies’ that seek to affix criminal liability on prominent personnel. In this light, this paper seeks to assess Sri Lanka’s TJ process, striving to balance competing demands of democracy, accountability, peace, and justice.
Keywords: Transitional justice; state responsibility; political instability; accountability; victims; reconciliation